Tubo-Ovarian Abscess Formation in Users of Intrauterine Devices Remote From Insertion: A Report of Three Cases - Marc R. Toglia; Joseph I. Schaffer (Hindawi Limited, 1996)
Background: The association between tubo-ovarian abscess formation and the presence of an intrauterine device (IUD) is well recognized. It has been suggested that the risk of upper-genital-tract infection is highest during the immediate period following the insertion of an IUD, returning to baseline by 5 months postinsertion. We present 3 cases of women who, 10-21 years after insertion of their IUDs, developed tubo-ovarian abscesses that were not causally related to sexually transmitted diseases (STDs) or actinomycetes.